Studi Tematik tentang Etika Politik dan Kepemimpinan Islam (Pendekatan Al-Qur’an dan Hadis) - Gendis Ayu Wulan M; Muhammad Alif; Mus’idul Milah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This paper discusses the study of politics from an Islamic perspective, which not only examines power and governance but also serves as a foundation for the development of political ethics rooted in the spiritual and moral values of the Qur'an and Hadith. The approach used is a literature review, analyzing relevant texts on Islamic politics, political ethics, and leadership concepts in Islam. In Islam, politics is regarded as a form of worship that must be carried out based on the principles of tawhid (monotheism), justice, shura (consultation), and social responsibility. Concepts such as khalifah (caliphate), shura, and maslahah (public interest) serve as key pillars in the ethical governance system aimed at the welfare of the ummah (community). Furthermore, this paper highlights the importance of political morality (akhlaq siyasah) as a moral foundation for leaders and political actors, while also exploring the distinction between ethics (akhlaq) and morality in the Islamic context. The findings indicate that integrating political studies with Islamic values can create a model of governance that is not only structurally strong but also morally and spiritually elevated. Thus, Islam offers a holistic normative framework for building a just and civilized political system.